The Belt and Road Initiative jako wyzwanie dla amerykańskich interesów w regionie Azji i Pacyfiku - Paula Tomaszewska; Sara Tomaszewska (Nowa Polityka Wschodnia, 2019)
The Asia-Pacific region occupies a key place in the international strategy of the United States. It was not without a reason that George W. Bush spoke about the “Pacific Century”, Barack H. Obama announced a strategic “pivot to Asia”, while Donald Trump went on a 12-day journey through East Asia. In particular, as the power of the People’s Republic of China increased, its importance gained a whole new dimension. At present, the USA and the PRC are conducting a sophisticated game on the “big Asia and Pacific chessboard”. China aspires to be an equal partner for economically and politically weakened United States. Assertively and unobtrusively, primarily with the use of diplomatic and economic instruments, China strengthens its international position. One of the manifestations of the expansion of Chinese influence in the world is growing and constant commitment to promoting the Belt and Road Initiative, which has become the most important symbol of the political ambition of President Xi Jinping. The article entitled “The Belt and Road Initiative as a challenge for American interests in the Asia-Pacific region” is an attempt at interdisciplinary consideration about the changing position of the Asia-Pacific region in foreign policy and US security strategy, as well as the consequences of the promoted BRI initiative for American interests. The basic research goal is to present, compare and explain the position of the administration of President Barack Obama and President Donald Trump against the Chinese concept of Belt and Road based on their adopted strategic documents, speeches and ongoing media discourse. The authors will consider how the United States reacted to the announcement by the President of the PRC of the Belt and Road initiative in 2013? Why and to what extent do the US counteract the Chinese concept of BRI?